SUBSTITUSI EKSTRAK DAUN KELOR TERHADAP MUTU ORGANOLEPTIK, KADAR FE, KAPASITAS ANTIOKSIDAN TERHADAP MINUMAN LATTE - Aditya Sintya Devy; Ni Putu Agustini; A.A. Nanak Antarini (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Moringa latte is a modification of coffee and milk products which are usually made with coffee raw materials which in this study added Moringa leaf extract and milk. This study was conducted to determine the organoleptic quality characteristics, Fe content and antioxidant capacity in Moringa latte. The research design used was Randomized Block Design (RBD) with five treatments and three replications. The treatment of the substitution of slurry of moringa leaves with pineapple porridge given is P1 (0%: 100%), P2 (5%: 95%), P3 (10%: 90%), P4 (15%: 85%) and P5 (20 %: 80%). The results showed that the treatment of Moringa leaf extract substitution and milk in Moringa latte with different concentrations had a very significant effect on color, aroma, taste, texture, aroma quality, texture quality, Fe content, antioxidant capacity. while the overall reception does not have a real effect on Moringa latte. From the results of an objective analysis of the resulting Moringa leaf jam, Fe content ranged from 0.00-5.53 (mg / L), the antioxidant capacity was 0.00-14.02 mg / L GAEAC. Moringa latte with the substitution of 20% Moringa leaf extract concentration produces the best latte that is most preferred by panelists, both in terms of color, aroma, texture, taste, overall acceptance and aroma quality with Fe content of 5.53 (mg / L) and antioxidant capacity 14 , 02 mg / L GAEAC. Keywords: Moringa latte, Fe content, antioxidant capacity